Circadian clock gene expression is impaired in gestational diabetes mellitus. (16th January 2013) - Pappa, Kalliopi I.; Gazouli, Maria; Anastasiou, Eleni; Iliodromiti, Zoe; Antsaklis, Aristides; Anagnou, Nicholas P.
Abstract: Dysfunction of the circadian clock genes is involved in the development of obesity and type 2 diabetes (T2D). Since gestational diabetes mellitus (GDM) and T2D share common genetic and phenotypic features, in the present study, we investigated the status of the circadian clock in a cohort of 40 Greek pregnant women with GDM, four with T2D and 20 normal controls. Peripheral blood mRNA transcript levels of 10 clock genes ( CLOCK1, BMAL1, PER1, PER2, PER3, PPARΑ, PPARD, PPARG, CRY1 and CRY2 ) were determined by real-time quantitative PCR. GDM patients expressed significantly lower transcript levels of BMAL1, PER3, PPARD and CRY2 compared to control women ( p < 0.05). No significant difference was documented between GDM women maintained either under insulin treatment or diet. A positive correlation was found between the expression of BMAL1 versus CRY2 ( r = 0.45, p = 0.003) and BMAL1 versus PPARD ( r = 0.43, p = 0.004). Further investigation on the functional relevance of these clock genes, disclosed that expression of PER3 correlated negatively with HbA1C levels ( r = −0.36, p = 0.022). These data document for the first time that the expression of BMAL1, PER3, PPARD and CRY2 genes is altered in GDM compared to normal pregnant women and support the notion that deranged expression of clock genes may play a pathogenic role in GDM.